Perceptions of alcohol misuse among Alaska native health care system stakeholders: A qualitative exploration. Issue 4 (2nd November 2020) - Trinidad, Susan Brown; Shaw, Jennifer L.; Dirks, Lisa G.; Ludman, Evette J.; Burke, Wylie; Dillard, Denise A.
Abstract: Although alcohol misuse is a priority for health care systems serving Alaska Native and American Indian (ANAI) people, stakeholders' perceptions of misuse are understudied. Patients ( n = 34), providers ( n = 20), and leaders ( n = 16) at a Tribally owned and operated health care system reported that alcohol misuse results from the interaction of factors, including colonization, structural factors, social alienation, social norms about overdrinking introduced at the time of colonizing contact, coping with emotions, and beliefs about ANAI people and alcohol. Childhood exposure to alcohol misuse leads some ANAI people to avoid alcohol altogether, shedding light on the high levels of abstinence observed in ANAI communities.